Analisis Pengalaman Pengguna dan Tingkat Kegunaan Aplikasi Mobile dan Website Shopee Menggunakan Pendekatan Human–Computer Interaction - Chaizura, Natasya; Natasya Chaizura; Junaidi Salat; Nurhidayani; Tursina; Uliya Safura (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Riau, 2025)
The rapid development of digital technology has driven the significant growth of e-commerce platforms as a widely used medium for online transactions. Shopee is one of the most widely used e-commerce platforms in Indonesia, accessible through both mobile applications and websites. This study aims to analyze the user experience and usability of the Shopee mobile application and website using a Human–Computer Interaction (HCI) approach. The research employs a quantitative method, with data collected through questionnaires distributed to active Shopee users. The aspects analyzed include ease of use, navigation efficiency, clarity of the user interface, and overall user comfort in interacting with the system. The results indicate that Shopee generally demonstrates a good level of usability, particularly in terms of ease of use and feature completeness. However, some users still experience difficulties related to interface consistency and navigation complexity in certain features. This study is expected to provide valuable insights for developers in improving the quality of user experience on e-commerce platforms.